Sustainable substrates for targeted nutrient delivery in urban farming - Maruthappan, Priadarsini (Nanyang Technological University, 2023)
There is tremendous interest in the development of alternative sustainable hydroponic substrates to replace currently unsustainable options. Utilising organic wastes in highvalue applications can promote sustainable agriculture through the formation of a circular economy loop. In this study, sugar-mediated porogen leaching was explored in keratin-based substrates that have been synthesised for use in a hydroponic setting. The aim was to obtain larger porous structures within the substrates to enhance plant growth, and this was achieved, with increasing sugar concentration resulting in larger porous structures within the substrates. Positive results were also obtained with respect to plant growth studies; however, the reflected data is not solely based on larger pores because the retention of sugars within the substrates also contributed to better plant growth profiles. Therefore, further development is required in the porogen leaching process to eliminate any residual sugars that are retained within the substrates so that more precise conclusions can be made regarding the effectiveness of sugar-mediated porogen leaching in keratin-based substrates.